Distribution of Bacterial Blight Resistance Genes in the Main Cultivars and Application of Xa23 in Rice Breeding - Wang, Shiguang; Liu, Wei; Lu, Dongbai; Lu, Zhanhua; Wang, Xiaofei; Xue, Jiao; He, Xiuying (Frontiers in Plant Science, 2020)
Bacterial blight (BB) is an important constraint on achieving a high and stable rice grain yield. An increasing number of BB resistance (R) genes have been identified and cloned to increase the available options for rice disease resistance breeding. However, it is necessary to understand the distribution of R genes in rice varieties for rational distribution and breeding. Here, we genotyped five R genes against BB in the seventy main cultivars from Guangdong Province, South China, using the corresponding specific markers. Our results showed that 87.1% of the tested varieties carried Xa4, and only three varieties carried Xa27, while no tested varieties carried Xa7, Xa21 or Xa23, which suggested that Xa4 was probably the most widely utilized R gene in rice breeding for BB resistance in Guangdong Province. Remarkably, Xa23, acting in a completely dominant manner, was found to effectively confer resistance against the strongly virulent BB strains of pathotype IX, which evolved quickly in southern China. Subsequently, we successfully bred two novel inbred rice varieties with strong restoration ability and two newly developed photoperiod- and thermo-sensitive genic male sterility (P/TGMS) lines using the broad-spectrum resistance gene Xa23 through marker-assisted selection (MAS) combined with phenotypic selection. All of the developed lines and derived hybrids exhibited enhanced resistance to BB with excellent yield performance. Our research thus sheds light on and may potentially facilitate both of the inbred and hybrid rice disease resistance breeding.